2021
DOI: 10.1080/0886022x.2021.1975741
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study comparing high and low balloon inflation pressure on technical success and patency for treating central venous lesions in patients on chronic hemodialysis

Abstract: Background We aimed to analyze the success rates and the access patency rates at 12 months between patients on chronic hemodialysis with symptomatic central venous stenosis (CVS) or occlusion (CVO), receiving high or low balloon inflation pressure for treatment. Methods We performed a retrospective study in which angioplasty balloons were inflated using a low-pressure or a high-pressure for the management of hemodialysis patients with CVS/CVO. The outcomes of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The success rate was 100% in CVS, whereas for those with CVO, the success rate was 79%. This agreed with that achieved by Cui et al, 32 and Horita et al, 33 A series of retrospective investigations revealed that angioplasty for CVS and CVO has a technical success rate of 70% to 90%. The fact that we achieved a 100% success rate for CVS was owing to our objective of dilatation of the vein simply to the extent that enabled cuffed catheter passage, rather than setting a target of less than 30% stenosis.…”
Section: Discussionsupporting
confidence: 90%
“…The success rate was 100% in CVS, whereas for those with CVO, the success rate was 79%. This agreed with that achieved by Cui et al, 32 and Horita et al, 33 A series of retrospective investigations revealed that angioplasty for CVS and CVO has a technical success rate of 70% to 90%. The fact that we achieved a 100% success rate for CVS was owing to our objective of dilatation of the vein simply to the extent that enabled cuffed catheter passage, rather than setting a target of less than 30% stenosis.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies demonstrated no significant differences in rupture rates between low inflation pressures (10-14 atm) and high inflation pressures (24-30 atm) when dilating central venous stenosis in hemodialysis patients. Considering these facts, clinicians should not hesitate to inflate balloons to high pressures, which may lead to better patency rates [21,22].…”
Section: Plos Onementioning
confidence: 99%